IPTV em rede xDSL e GPON - Santana, André Ferreira (2016)
The telecommunications networks in Brazil are mostly quite old and the huge country's size makes network maintenance and a evolution of technology a costly process. This research is an approach to the provision of pay TV service in xDSL and GPON network. Besides the theoretical analysis, tests were performed in real networks, of a telecommunications company in Curitiba, to understand the behavior of the access network and service availability in practice. This work presents concepts of telecommunications networks to the end user, history and access technology of the pay TV service. The results show that it is feasible to use the xDSL networks to provide the IPTV service, if the distance limitations are considered. This way, TV operators do not require to replace their twisted par-based by optical fiberbased access networks to provide this kind of service. However, the results with GPON networks enable a more reliable service and of better quality.